“Das Eine Ist Verbunden Mit Gott, Das Andere Aber Auch”: Service Provision as Part of Religious Life in an Eritrean Orthodox Community in Berlin, Germany - Susanna Trotta (Religions)
Despite a growing body of academic literature on religion and migration, there is limited focus on the roles of migrant religious communities and on how religious everyday practices intersect with migration and its implications. This study seeks to address these issues from a post- and decolonial perspective, through the analysis of the activities of the St. Georgis Eritrean orthodox church in Berlin. It draws on material collected through semi-structured interviews, participant observation, and primary text analysis between 2023 and 2024. Some of the main findings include the fact that the church provides a range of services to its members, e.g., family conflict resolution sessions and specific meetings for families with children with disabilities, which address some of the issues that the community itself chooses to prioritise and that are not addressed by other service providers. Analysing the establishment of the church and its social activities, this article focuses on the agency of the congregation and how it challenges Northern/Western religion and migration frameworks, with a specific focus on its religious dimension.